Development of a modified BEMT model for the analysis of helical bladed vertical axis tidal turbines (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Development of a modified BEMT model for the analysis of helical bladed vertical axis tidal turbines Mohammad Fereidoonnezhad1, Seán Leen1, Stephen Nash1, Tomas Flanagan2, Patrick McGarry11 School of Engineering, University of Galway, Galway, Ireland2 ÉireComposites Teo., Údarás Industrial Estate An Choill Rua, Inverin, Galway, IrelandE-mail: patrick.mcgarry@universityofgalway.ie   Keywords: Blade element momentum theory, Helical vertical axis tidal turbine, FEA AnalysisClassical blade element momentum theory (BEMT) formulations are not capable of accurately simulating complex blade geometries, such as spiral or helical blade geometries. In this paper, we develop a modified BEMT model to calculate hydrodynamic forces acting on the helical vertical axis tidal turbines. Our framework accounts for curved blade geometries where the leading edge is not orthogonal to the freestream velocity, and chord vectors are not in the azimuthal-radial plane. We validate the model using experimental data for a prototype VAWT. We then perform a parametric analysis of helical bladed VATT designs. Both the helix angle of the blade and the relative orientation of the chord strongly influence the power output of a turbine. Our modified BEMT model also predicts that an increase in blade helix angle results in reduced power fluctuations. Additionally, computed fluctuations in tangential and normal forces acting on blades are shown to reduce significantly with increasing blade helix angle, suggesting a reduction in risk of fatigue failure. We also uncover a complex distribution of normal and tangential forces along the length of a helical blade. Fluctuating hydrodynamic forces computed by our modified BEMT model are input into a finite element (FE) framework to compute the stress state in a fibre reinforced composite blade material for a range of blade azimuthal positions. Analyses reveal that blade deflections are three orders of magnitude lower than the turbine radius, suggesting that sufficient structural stiffness is achieved by the blade design. Results also uncover stress concentrations in the region of strut-blade connection, revealing a higher risk of fracture and fatigue failure at this location.